How Does Public Service Motivation Explain Knowledge Sharing Behavior among Indonesian Civil Servants? - Danang Fauzan; Rachmadi Triono; Zuliani Dalimunthe (Jurnal Bina Praja, 2022)
The Indonesian government conducted bureaucratic reforms to create excellent and clean governance. The reforms need government institutions to utilize the wealth of knowledge they have. However, knowledge is still scattered among institutions employees and not well documented. Thus, it is critical to apply knowledge management, especially to share the knowledge. This study aims to determine the antecedents that influence knowledge-sharing behavior among Indonesian civil servants (Aparatur Sipil Negara, ASN), especially in the finance ministry, which is the scope of this research. This research analyzes the effect of job autonomy on knowledge-sharing behavior. This study also examines the mediating role of public service motivation and intrinsic motivation. We spread the questionnaire across seven echelons III working units in the headquarters of the finance ministry. The researchers limited respondents to work periods of more than one year and collected 252 valid responses. The researchers captured respondents' perceptions of the overall research variables and processed the data using structural equation modeling with AMOS software. The results showed that job autonomy positively affects public service motivation and intrinsic motivation. However, there is not enough evidence to conclude that there is significant knowledge-sharing behavior between ASN evaluated here unless there is a need to provide public service. This finding indicates that Indonesian ASN would not share their knowledge voluntarily. We also found no difference in the behavior between millennial ASN and their senior counterparts. We suggest that the administration design a working procedure with enough autonomy to push the ASN to share their knowledge.